Albumin and neutrophil to lymphocyte ratio as predictors of tumor stage in patients with gastric cancer: Albumina e índice neutrófilo-linfocito como predictores de estadío tumoral en pacientes con cáncer gástrico - O. Huamán, Manuel (2020)
Introduction: Gastric cancer is a public health problem worldwide. Objective: To determine the association between albumin, inflammatory markers and tumor stage of gastric cancer patients in a National Hospital of Peru. Methods: An observational, analytical and retrospective study corresponding to the 2017 and 2018 years. The frequencies and distribution of the variables were evaluated: clinical stage according to the AJCC 2018, albumin as a nutrition indicator and Neutrophil Lymphocyte-Ratio (NLR) as an indicator of inflammatory and immune response. The value 2.44 was taken as the cut-off point for high NLR. Results: Were included 96 patients. The average age was 63.5 years ± 12.8, the male: female ratio was 1: 1, 80.2% came from the region of the coast of Peru; 70.8% had an advanced clinical stage and 85.4% corresponded to tumor size T3 and T4. 64% presented undifferentiated histological grade and 30.1 showed evidence of metastasis. The mean NLR was 2.94 ± 1.7, and albumin was 3.64 g / dl ± 0.6. In the bivariate analysis, a significant association was found between the high level of NLR and the advanced clinical stage (OR: 4.46 95% CI 1.65-13.27 p <0.001), and between low levels of serum albumin with advanced stage (OR: 13.02 95% CI 1.78-563.36 p <0.005). Conclusion: A late diagnosis was found in 70% of the patients. High NLR as an indicator of inflammatory response and low albumin as an indicator of nutrition are predictors of advanced clinical stage in gastric cancer.